Peran Pembelajaran Sejarah Membentuk Karakter Siswa (Studi Kasus SMA Mulia Pratama) - Wahyuni Tri Hapsari Harahap; Enike Br Tarigan; Lidia Banjarnahor; Yushar Tanjung (BEST Journal (Biology Education, Sains and Technology), 2022)
Education plays an important role for the development of students to shape the character of human beings, citizens, and good citizens. The problem currently experienced by the Indonesian nation is a moral crisis that has begun to arise and result in the Indonesian nation losing its true character and identity as stated in Pancasila. The character of the Indonesian nation emerged when the heroes fought to obtain the independence of the Indonesian state. Therefore, to be able to shape the character of students in the world of education in order to become a good Indonesian nation, a way is needed to make it easier for educators to instill character in their students. The role of history learning can be used as a way to shape the character of the Indonesian nation. With history learning, teachers can show attitudes that should be exemplified when heroes fought for Indonesian independence. Historical lessons play a role in shaping the character of the nation to foster an attitude of nationality and love for the homeland. Teachers must be able to put themselves in place to inspire students to have a good national character through history learning.